Philosophy's Contribution to Cultural Transformation in The Era of Technological Revolution - Anggraeni, Sylvia; Sadiyah, Nurhalimatus; Mahardika, I Ketut; Suratno, Suratno (Peneliti.net, 2024)
The Fourth Industrial Revolution, with disruptive technologies such as artificial intelligence, IoT, and big data, brings significant changes to the way we live, work, and our cultural values. Philosophy plays a crucial role in preserving fundamental values, ensuring that culture remains adaptable without losing its essence amidst these transformations. Through a critical approach, philosophy aids in designing an inclusive and humanistic future, addressing ethical, epistemological, and ontological challenges. In ethics, philosophy tackles issues like privacy, algorithmic bias, and social inequality through deontological and utilitarian approaches. In epistemology, it promotes digital literacy to distinguish between true and false information, while in ontology, it explores the impact of technology on identity and reality. Furthermore, philosophy contributes to cultural transformation by promoting sustainability and preserving local heritage, guiding technology and culture toward a more just and sustainable future.